2013
DOI: 10.2461/wbp.2013.ibeun.3
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal record of Wild boar (Sus scrofa) in northeast Spain: Implications for implementing disease-monitoring programs

Abstract: The wild boar population in Spain has increased in recent decades due to a number of factors, including increased food availability, the abandonment of crops, as well as through hybridization with the domestic pig. Studying dispersal is useful for understanding the ecology of a species and the spread of diseases in wildlife. In the case of the wild boar (Sus scrofa), its dispersal depends on environmental changes, food availability, population density, and hunting pressure. The goal of this study was to descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
3
15
1
Order By: Relevance
“…where 11 serotypes were detected. This fact is probably reflecting the free nature of the carrier animal and its habit of frequent moving for long distances (Andrzejewski & Jezierski, 1978;Casas-Díaz et al, 2013). In this way, the present study also shows the wide spread of Salmonella spp.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…where 11 serotypes were detected. This fact is probably reflecting the free nature of the carrier animal and its habit of frequent moving for long distances (Andrzejewski & Jezierski, 1978;Casas-Díaz et al, 2013). In this way, the present study also shows the wide spread of Salmonella spp.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast to most of the literature on pigs (Baloda, Christensen, & Trajcevska, ; Berends, Urlings, Snijders, & Van Knapen, ; Hurd, McKean, Wesley, & Karriker, ; Letellier, Messier, Pare, Menard, & Quessy, ), our data showed that the animals from the majority of the estates carried more than one serotype, reaching its maximum in F14, where 11 serotypes were detected. This fact is probably reflecting the free nature of the carrier animal and its habit of frequent moving for long distances (Andrzejewski & Jezierski, ; Casas‐Díaz et al., ). In this way, the present study also shows the wide spread of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile male wild boar will probably leave their maternal group during the mating season, generating a dispersal peak in autumn (Keuling et al, 2008). However, long-range movements of older wild boar have also been recorded (Casas-D ıaz et al, 2013). Hence, long-range movements may occur in any season.…”
Section: Wild Boar Ecologymentioning
confidence: 99%
“…For instance, risk assessment models for the introduction/spread of African Swine Fever are heavily dependent on parameters regarding the land occupation (De la Torre et al, 2015). Surveillance programs for commercial swine herds often consider the dynamics of the wild boar population in preventing diseases (Casas-Díaz et al, 2013). As such, the models proposed here are useful for generating inferences about dispersal distance and testing if covariates are associated with the distance, thus helping to overcome current gaps in our understanding of wild boar behavior (Guinat et al, 2016;EFSA, 2019).…”
Section: Discussionmentioning
confidence: 99%